2021
DOI: 10.1115/1.4051035
|View full text |Cite
|
Sign up to set email alerts
|

An Energy Efficient Power-Split Hybrid Transmission System to Drive Hydraulic Implements in Construction Machines

Abstract: This paper proposes a novel hybrid power-split transmission to drive hydraulic implements in construction machinery. The highly efficient power-split hybrid transmission is combined with displacement controlled (DC) actuators to eliminate throttling losses within the hydraulic system and achieve higher fuel savings. The architecture design, sizing and power management are addressed. Simulation results considering a realistic truck-loading cycle on a mini excavator demonstrate the feasibility of the idea. A sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In this case, the carrier is connected to the engine, the sun is connected to the primary unit and ring is connected to the load. The sizing procedure for the hydrostatic units and accumulator is left out of this paper for brevity, but the reader is invited to refer to this previous publication 8) for details on the sizing method. However, it is important to highlight that the system is sized such that the power of the original system can always be delivered to the LS pump, even when the accumulator pressure is minimum.…”
Section: Planetary Gear Configuration Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the carrier is connected to the engine, the sun is connected to the primary unit and ring is connected to the load. The sizing procedure for the hydrostatic units and accumulator is left out of this paper for brevity, but the reader is invited to refer to this previous publication 8) for details on the sizing method. However, it is important to highlight that the system is sized such that the power of the original system can always be delivered to the LS pump, even when the accumulator pressure is minimum.…”
Section: Planetary Gear Configuration Selectionmentioning
confidence: 99%
“…Williamson 7) showed that by varying the engine speed this problem can be solved, but nevertheless, the engine is forced to constantly vary its speed moving away from its optimal operating point during high flow-demand. To address this issue, a power-split hydraulic hybrid transmission between engine and hydraulic pumps was first proposed by the authors in a recent work 8) . With this approach, DC pumps and engine speeds can be controlled independently, leading to fuel consumption improvements of up to 60% when compared to the baseline Load-Sensing system or extra 11% when compared to the previous version of the hybrid system.…”
Section: Introductionmentioning
confidence: 99%
“…Their applications include hybrid vehicles (Costa and Sepehri, 2015;U.S. Environmental Protection Agency, 2020;Pourmovahed et al, 1992;Deppen et al, 2012;Deppen et al, 2015;Beachley et al, 1983;Ho and Ahn, 2010;Chapp, 2004;Chen et al, 2022;Sprengel and Ivantysynova, 2013), wind and wave energy extraction (Dutta et al, 2014;Fan et al, 2016a;Fan et al, 2016b;Fan et al, 2016c;Irizar and Andreasen, 2017;Fan and Mu, 2020), excavators and machinery alike (Heybroek et al, 2012;Lin and Wang, 2012;Shen et al, 2013;Hippalgaonkar and Ivantysynova, 2016a;Hippalgaonkar and Ivantysynova, 2016b;Ren et al, 2018;Yu and Ahn, 2020;Bertolin and Vacca, 2021). Accumulators have also been used as low-pressure tanks in closed hydraulic circuits (Çalışkan et al, 2015;Costa and Sepehri, 2019), shock absorbers (Porumamilla et al, 2008), and as part of switched hydraulic circuits, where hydraulic power at the actuator is controlled by fast-switching hydraulic valves instead of spool valves (to reduce throttling losses) (Brown et al, 1988;De Negri et al, 2014;Kogler and Scheidl, 2016;Yudell and Van de Ven, 2017).…”
Section: Introductionmentioning
confidence: 99%